Collegial Interaction in the Babylonian Talmud - Kalmin, Richard (The Jewish quarterly review, 1992)
Contemporary amoraim frequently interacted with one another. Their interactions as recorded in the Babylonian Talmud are not the product of the talmudic editors but are "real," i.e., historical. Frequently the masters were not just contemporaries but also colleagues, that is, teachers of students. Collegial interactions were frequently formal (not by chance, not episodic) and hierarchical (with a clear sense of inferior/superior, not a relationship between equals). The judicial and rabbinic hierarchies were distinct in the first two amoraic generations but were unified in the third and following generations. Again, the talmudic portrayal accurately reflects historical reality, or at least a change in perception on the part of the rabbis, and is not an invention by late pseudepigraphers.